Detection of immunoglobulin heavy chain gene rearrangements in Hodgkin's disease using PCR. Issue 10 (October 1993) - Angel, C A; Pringle, J H; Primrose, L; Lauder, I
Abstract : AIM--To detect clonal rearrangements of the immunoglobulin (Ig) heavy chain gene in Hodgkin's disease tissue using the polymerase chain reaction (PCR). METHODS--DNA extracted from 36 samples of Hodgkin's disease was analysed using PCR and primers from conserved sequences in the variable (VH) and joining (JH) regions. RESULTS--Clonal rearrangement was detected only in one case. Evidence of clonal immunoglobulin gene rearrangement had been detected previously in this case using conventional Southern blot analysis. CONCLUSIONS--The sensitivity of the two techniques is equivalent and clonal Ig heavy chain gene rearrangements are rare in Hodgkin's disease.